Vivir con voces en la infancia: contenido, influencia y estrategias de recepción - de Souza Cardoso, Clarissa; Antunes Machado, Roberta; Streicher Janelli da Silva, Marta Solange; Leal Argiles, Carmem Terezinha; Prado Kantorski, Luciane; Christello Coimbra, Valéria Cristina (Pontificia Universidad Católica del Perú, 2024)
Identify content, influence and strategies for welcoming the experience based on the narrative of children who hear voices. Method: narrative-qualitative study, Benjaminian concepts of experience and language were used to analyze the contributions of four children, aged between nine and 12 years old, self-declared voice hearers. Results and discussions: they presented friendly voices as content that positively influenced daily life, while voices difficult to deal with induced social distancing. The strategies developed were: Reiki practice, participation in the Group, literary writing, drawing, online games. Final considerations: The contents can include voices, visions, and sensations; the influence is attributed to introspection and insecurity, and one of the strategies was the United Children Group.

Identifier contenu, l’influence et les stratégies d’accueil de l’expérience basées sur le récit d’enfants qui entendent des voix. Étude narrative-qualitative, les concepts benjaminiens d’expérience et de langage ont été utilisés pour analyser les contributions de quatre enfants, âgés de neuf à 12 ans, auditeurs autoproclamés de voix. Les voix amicales comme des contenus qui influençaient positivement la vie quotidienne, tandis que les voix difficiles à gérer induisaient une distanciation sociale. Les stratégies développées étaient pratique du Reiki, participation au Groupe, l’écriture littéraire, dessin, les jeux en ligne.: Les contenus peuvent être des voix, des visions et des sensations; l’influence est attribuée à l’introspection et à l’insécurité, et l’une des stratégies était le Groupe Enfants Unis.

Identificar conteúdo, influência e estratégias de acolhimento a partir da narrativa de crianças que escutam vozes. Método: estudo narrativo-qualitativo utilizou-se conceitos Benjaminianos de experiência e linguagem, analisaram-se as contribuições de quatro crianças, com idades entre nove e 12 anos autodeclaradas ouvidores de vozes. Realizaram-se as atividades com a criação do grupo online Crianças Unidas. Resultados e discussões: apresentaram como conteúdos vozes amigáveis que influenciaram positivamente no cotidiano, enquanto as vozes difíceis de lidar induziram ao distanciamento social. As estratégias desenvolvidas foram: prática do Reiki, participação no Grupo, escrita literária, desenhar, jogos online. Considerações finais: os conteúdos podem ser vozes, visões e sensações; a influência é atribuída à introspecção e insegurança e uma das estratégias foi o Grupo Crianças Unidas.

Identificar contenidos, influencias y estrategias de acogida de la experiencia a partir de la narrativa de niños que escuchan voces. Método: estudio narrativo-cualitativo, se utilizaron conceptos benjaminianos de experiencia y lenguaje para analizar las contribuciones de cuatro niños, con edades entre nueve y 12 años, auto-declarados oyentes de voz. Resultados y discusiones: presentaron voces amigas como contenidos que influyeron positivamente en la vida cotidiana, hubo distanciamiento social con voces difíciles de manejar. Las estrategias desarrolladas fueron: práctica de Reiki, participación nel Grupo, escritura literaria, dibujo, juegos online. Consideraciones finales: Los contenidos pueden ser voces, visiones y sensaciones; la influencia se atribuye a la introspección y la inseguridad, y una de las estrategias fue el Grupo Niños Unidos.
Living with voices in childhood: content, influence and reception strategies
Vivre avec des voix dans l’enfance: contenus, stratégies d’influence et de réception
Keywords: Mental health assistance; Child health; Hearing voices; Movement International Hearing Voices; Atención a la salud mental; Salud de niños; Escuchar voces; Movimiento Internacional de Escuchar Voces; Soin de la santé mentale; La santé de l’enfant; Auditeurs de voix; Mouvement international des voix entendues; Assistência à saúde mental; Saúde da criança; Ouvidores de vozes; Movimento Internacional de Ouvidores de Vozes; https://purl.org/pe-repo/ocde/ford#5.01.00